Pornography use and sexism among heterosexual men. Issue 3 (26th May 2020) - Miller, Dan J.; Kidd, Garry; Raggatt, Peter T. F.; McBain, Kerry Anne; Li, Wendy
ABSTRACT: The idea that pornography promotes sexism is a commonly purported one. This study employed an online sample of heterosexual men ( N = 323) to investigate the relationship between pornography use (in terms of both overall level of pornography use and use of violent and/or humiliating pornography) and old-fashioned and modern sexism. The moderating effects of agreeableness and perceived realism of pornography were also assessed. Level of general pornography use and use of violent and/or humiliating pornography was not predictive of either sexism measure. Agreeableness was negatively predictive of both sexism measures, whereas perceived realism was positively predictive of sexism. Agreeableness and perceived realism did not moderate the relationship between level of pornography use and any of the outcome measures.